Control of sonic nozzle flow with D-Shaped Rib with sudden expansion: a comprehensive CFD approach - Newaz, Md Ashif; Bellary, Syed Ahmed Imran; Khatawate, Vinayak Hanmantasa; Monis, Renita Sharon; Shetty, Shamitha; Khan, Sher Afghan; Jilani, Shaikh Sarfaraj (istoriya Journal, 2025)
The development of space shuttles and high-performance military aircraft has made studying turbulent flow in a separated region a vital topic of study. Researchers are also interested in turbulent flow in transonic and supersonic flow. There is considerable relief for the flow when it separates and expands once the area of the larger duct suddenly increases. There are two areas where the shear layer emerges: the separated flow and the main flow. Considerable drag results from the split streamline reattaching to the duct, creating a recirculation zone where the pressure is lower than the surrounding air. Flow from a converging nozzle is suddenly exhausted to a larger diameter. The duct diameter is 22 mm. Base pressure management using a D-shaped rib as a passive control mechanism is the primary focus of this study. The passive control was located at various positions, with a length-to-diameter ratio (L/D) of 0.5, 1, 1.5, 2, and 3. Numerical simulations were conducted for 0.5, 1, and 1.5 mm rib radii. Results indicated that the D-shape rib with a 0.5 mm radius is ineffective, except at nozzle pressure ratios of 4 and 5. The maximum increase in the base pressure is attained for a rib radius of 1.5 mm, and a very moderate rise is obtained for a 1 mm radius. It is observed that the rib locations at L/D = 2 and 3 are ineffective, as the flow becomes attached to the wall around L/D = 1 to 1.5. Hence, one can select the rib radius and height based on the user's requirements.